ARE FOOD WASTE AND FOOD LOSS A REAL THREAT FOR FOOD SECURITY? - Mirela PARASCHIVU; Otilia COTUNA; Gheorghe MATEI; Veronica SĂRĂȚEANU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Food loss and waste is a global issue worldwide, posing a real challenge to both food security and sustainability. The productivity of our food system is reduced by food loss and waste, which can result in lower incomes for farmers and higher costs for food consumers. Food loss and waste occur at different levels along the food chain supply in production, postproduction procedures, processing, distribution and consumption. Concrete targets to reduce food loss and waste are necessary to be set at country levels focused on specific particularities. Thus, for developed countries the focus should be on waste, while for developing countries the focus should be on food loss, but also considering best solutions for reducing food waste in the future. The present review considers the most important data and relevant literature on this topic in order to offer significant insights and to identify knowledge gaps within literature. The present research should increase the interest for multifaced solutions to reduce food loss and waste in order to increase food security. Thus, short and long term solutions refer to proper identification of food loss and waste gaps along food chain supply, e-commerce platforms for products marketing, rethinking standards on aesthetic requirements for fruits and vegetables, shorter value chain in order to put the farmers in direct contact with markets and consumers, improved packaging during transport of fresh products, investing in agtech, biotechnology, smart packaging and consumers’ education in using food and food-related resources more efficiently.